Riflessioni sul demiurgo in Plotino a partire dall’interpretazione del Timeo e dell’Epinomide - Volpe, Enrico (Peitho. Examina Antiqua, 2024)
The problem of the interpretation of the Timaeus represents one of the greatest exegetical challenges for Plotinus. For Plotinus the Timaeus is a problematic dialogue due to its mythical-allegorical language and the fact that some doctrines in the work seem incompatible with his hypostatic vision. The Plotinian conception of the demiurge is critical of the concept of “artisanal causality.” Plotinus does not agree that the cosmos could have been generated according to a plan, i.e., according to dianoetic and contingent reasoning. At the same time, he identifies the demiurge with the Intellect, but then, in other treatises, also equates the demiurge with the world soul and nature, i.e., the aspect of the third hypostasis that has the task of acting directly on matter. While this ambiguity of Plotinus is found in several places of his Enneads, it finds justification in a spurious dialogue of Plato, the Epinomis, in which the role of the demiurgic soul is central. In my opinion, Plotinus is likely to have taken his cue from the Epinomis as an endorsement for his doctrine of the demiurgic soul. Nevertheless, the fact remains that the identification of the demiurgic soul with a single hypostasis leads Plotinus to several aporias.